LGBT and Religious Negotiations: A Case Study of Youth Interfaith Forum on Sexuality (Yifos) - Roni Roni (Al-Albab, 2022)
Most religious perspectives, particularly the conservative interpretation, emphasize the incompatibility of being a Lesbian, Gay, Bisexual or Transgender (LGBT) and being religious. This contradiction creates internal conflicts for many LGBT individuals. In social and political spheres, many religious groups post hostility and rejection against the LGBT using the justification of their religious dogma. The position of the LGBT has been more vulnerable since the reformation period (1998 to present) in Indonesia, during which Islamic conservatism is rising. Therefore, LGBT individuals perceive themselves as condemned and excluded from religious communities. Nevertheless, the existing LGBT communities and organizations focus more on campaigning social acceptance and public recognition through a human rights perspective. This research employs a qualitative method and addresses the Youth Interfaith Forum of Sexuality (YIFoS) in providing a ‘safe space’ for the LGBT in negotiating their non-normative sexuality and religious values. Taking a case study of YIFoS, I argue that LGBT could also embrace their religiosity. Through the concept of ‘liberation of the body and alternative religious interpretations, YIFoS believes that LGBT sexuality could be reconciled with religion.  This research is divided into two parts. First is how YIFoS provide a way of reconciling of non-normative sexuality of LGBT and religion. Second is what approach is employed by YIFoS in helping LGBT individuals negotiate their non-normative sexuality and religious values. My findings demonstrate that the YIFoS applies the concept of ‘experience of the body as the main departure of liberation and employs an interfaith approach by inviting religious figures whose interpretations are more accommodative toward LGBT. The interfaith approach is aimed at building commonality on LGBT within religious communities. In addition, these two approaches are used to help LGBT individuals to stimulate self-acceptance and personal reconciliation between one’s religious values and their non-normative sexuality.